COVID‐19 and plasma cells: Is there long‐lived protection?. Issue 1 (8th July 2022) - Nguyen, Doan C.; Lamothe, Pedro A.; Woodruff, Matthew C.; Saini, Ankur S.; Faliti, Caterina E.; Sanz, Ignacio; Lee, Frances Eun‐Hyung
Summary: Infection with SARS‐CoV‐2, the etiology of the ongoing COVID‐19 pandemic, has resulted in over 450 million cases with more than 6 million deaths worldwide, causing global disruptions since early 2020. Memory B cells and durable antibody protection from long‐lived plasma cells (LLPC) are the mainstay of most effective vaccines. However, ending the pandemic has been hampered by the lack of long‐lived immunity after infection or vaccination. Although immunizations offer protection from severe disease and hospitalization, breakthrough infections still occur, most likely due to new mutant viruses and the overall decline of neutralizing antibodies after 6 months. Here, we review the current knowledge of B cells, from extrafollicular to memory populations, with a focus on distinct plasma cell subsets, such as early‐minted blood antibody‐secreting cells and the bone marrow LLPC, and how these humoral compartments contribute to protection after SARS‐CoV‐2 infection and immunization.